Strategies for monetary cooperation/union - Zahler, Roberto (2001)
Highlights the conditions necessary for successful implementation of a cooperative medium-term strategy among developing countries. Suggests some courses of action that the countries should adopt in seeking to coordinate their macroeconomic policies to the point that they secure advanced forms of convergence. Offers some guidelines for monetary coordination among countries that are integrating, and underscores the limitations imposed by capital flows on exchange rate coordination. Concludes with a proposal for macroeconomic coordination among Latin American countries.